2007
DOI: 10.21273/jashs.132.6.850
|View full text |Cite
|
Sign up to set email alerts
|

Plum Pox Virus Coat Protein Gene Intron-hairpin-RNA (ihpRNA) Constructs Provide Resistance to Plum Pox Virus in Nicotiana benthamiana and Prunus domestica

Abstract: Constructs with self-complementary sequences separated by an intron produce “hairpin” RNA [intron-hairpin-RNA (ihpRNA)] structures that efficiently elicit posttranscriptional gene silencing (PTGS). In the current study, the authors use this technology to confer resistance to plum pox virus (PPV) in herbaceous and woody perennial plants by silencing the PPV–coat protein (CP) gene. The authors confirmed the high capacity of ihpRNA constructs for inducing RNA silencing in Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 48 publications
7
64
0
1
Order By: Relevance
“…A longer hpRNA sequence is more efficient than a shorter one. Similar results were presented in tobacco (Chen et al, 2004), tomato (Praveen et al, 2009) and some herbaceous and woody perennial plants (Hily et al, 2007). Further study is necessary to clarify whether the length of the hpRNA sequences or their different target regions in the same gene brought about the different interference efficiency to virus gene expression.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A longer hpRNA sequence is more efficient than a shorter one. Similar results were presented in tobacco (Chen et al, 2004), tomato (Praveen et al, 2009) and some herbaceous and woody perennial plants (Hily et al, 2007). Further study is necessary to clarify whether the length of the hpRNA sequences or their different target regions in the same gene brought about the different interference efficiency to virus gene expression.…”
Section: Discussionsupporting
confidence: 69%
“…This is usually attributed to the influence of the length and integration patterns of the transgenic inverted-repeat sequences to the efficiency of RNAi (Yin and Wang, 2000;Wesley et al, 2001;Di Nicola-Negri et al, 2005;Zhu et al, 2005;Rai et al, 2007;Clarke et al, 2008), and RNAi suppress protein (Mallory et al, 2001;Savenkov and Valkonen, 2002;Kubota et al, 2003;Love et al, 2007). A longer hpRNA expressed by the transgenic inverted-repeat sequence was found to be more effective to silence virus gene than a shorter one (Chen et al, 2004;Hily et al, 2007;Praveen et al, 2009), although the short limit of the transgenic inverted-repeat sequence for RNAi was found to be ∼20 bp (Qu et al, 2007). On the other hand, the integration of the exotic expression constructs themselves, especially transformed by Agrobacterium mediation, can induce chromosomal rearrangement including translocation, inversion, deletion and insertion (Azhakanandam et al, 2000;Yin and Wang, 2000;Rai et al, 2007;Zeng et al, 2010;Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On transcription, the resulting hairpin RNA acts as a strong inducer of post-transcriptional gene silencing (PTGS) (Smith et al, 2000). This strategy has been used to produce virus-resistant transgenic plants (Helliwell and Waterhouse, 2003;Hily et al, 2007;Kreuze et al, 2008;Prins et al, 2008;Shimizu et al, 2009;Fahim et al, 2010), with the accumulation of transgene-derived siRNAs being regarded as a predictor of resistance to virus infection (Kalantidis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…1) showed that gene constructs encoding intron-spliced hairpin RNAs (ihpRNAs) can induce RNA silencing with high efficiency (>90%) opening the way on how to effectively apply RNA silencing technology to obtain virus-resistant plants. 117 In order to develop robust tools for inducing PPV resistance, that are not highly dependent on a particular and uncontrolled event of transformation, PPV-derived constructs based on the ihpRNA technology 117 were developed using isolates of PPV-D [118][119][120][121] or -M strain. 122 Pandolfini et al utilized a short (Fig.…”
Section: Transgenic Strategies To Control Ppv Infectionmentioning
confidence: 99%
“…Hily et al 120 reported that four ihpRNA constructs, harboring the full length or the second half of the CP gene (Fig. 1), under the transcriptional control of either CaMV 35S or peach Cab promoters, were introduced in N. benthamiana plants.…”
Section: Transgenic Strategies To Control Ppv Infectionmentioning
confidence: 99%